Case report: MOG-IgG-associated encephalitis with Epstein-Barr virus infection and Alzheimer's pathologic change in cerebrospinal fluid - Li, Lin; Li, Chuan; Yao, Dan; Hao, Yun-feng; Zhao, Chao; Yan, Qi; Liu, Jun-tong; Liu, Shu-yu; Zhu, Wen-ping; Du, Ying; Zhang, Wei (Frontiers in Neurology, 2022)
Immunoglobulin G antibodies to myelin oligodendrocyte glycoprotein (MOG-IgG) associated disease is a rare demyelinated disease in central nerve system (CNS) predominately involving optic nerve, spinal cord and brain leading to optic neuritis (ON), transverse myelitis (TM), encephalitis. The phenotype of MOG-IgG associated encephalitis is similar to acute disseminated encephalomyelitis (ADEM) presenting with seizures, abnormal behavioral and psychological symptoms, cognitive impairment. A few brain biopsies show a multiple sclerosis (MS) pattern histopathology with T cells, macrophages, and complement activation. To date, how MOG-IgG produces is unknown. Herein, we report a case of a 32-year-old male with MOG-IgG associated encephalitis presenting with MOG-IgG positive in cerebrospinal fluid (CSF) but seronegative, as well as Epstein-Barr virus (EBV) infection and Alzheimer's pathologic change in CSF (Aβ1−42 = 317 pg/ml, T-Tau = 538 pg/ml, p-Tau =10.09 pg/ml). A combination treatment of administering intravenous immunoglobulin (0.4mg/kg.d, 5 days) and low-dose of methylprednisolone (80mg/d, 5 days) and rituximab (100mg/week, 3 weeks), the patient recovered significantly after 3 months follow-up. This case supplies us new thoughts into the production of MOG-IgG and the possible pathologic mechanism of MOG-IgG associated disease (MOG-AD), and simultaneously further confirms the interaction between EBV and changes of CSF biomarkers of Alzheimer’s disease (AD).